Successful Reperfusion Using Mechanical Aspiration Thrombectomy in ST-Segment Elevation Myocardial Infarction with an Ectatic Right Coronary Artery: A Case Report - Singha, Chayan Kumar; Mahmud, Sohel; Haque, Mostashirul; Khaled, Fakhrul Islam; Rahman, Md Walidur; Saha, Sujoy Kumar; Majumder, Mohammah Harun Or Rashid; Mahmood, Manzoor (University Heart Journal, 2025)
A Coronary artery ectasia predisposes to thrombus formation through disturbed flow and blood stasis, fulfilling a key component of Virchow’s triad, and may result in acute myocardial infarction with a high thrombus burden. The aim of primary percutaneous coronary intervention (PPCI) is restoration of both epicardial coronary flow and myocardial reperfusion. Although routine thrombus aspiration is not recommended, selective use may be beneficial in patients with extensive intracoronary thrombus. We report a 60-year-old diabetic and hypertensive man presenting with acute inferior wall myocardial infarction, in whom coronary angiography demonstrated diffuse ectasia of the right coronary artery and its branches with a massive thrombus in the posterior left ventricular branch. Following administration of unfractionated heparin and eptifibatide, multiple passes of manual aspiration thrombectomy using a Medtronic Export Advance catheter resulted in successful thrombus removal, restoration of coronary flow, and complete ST-segment resolution, highlighting the potential role of selective aspiration thrombectomy during PPCI in ectatic coronary arteries with high thrombus burden. University Heart Journal 2025; 21(2): 92-95